A camptothecin prodrug induces mitochondria-mediated apoptosis in cancer cells with cascade activations. Issue 84 (5th October 2021) - Luo, Xiangjie; Chi, Xiaoqin; Lin, Yaying; Yang, Zhaoxuan; Lin, Hongyu; Gao, Jinhao
Abstract : A photosensitizer-conjugated camptothecin (CPT)-based prodrug was developed for combinative chemo-photodynamic treatment of solid tumors with cascade activations. Abstract : Mitochondria are crucial regulators of the intrinsic pathway of apoptosis. Herein, we report a photosensitizer-conjugated camptothecin (CPT)-based prodrug for combinative chemo-photodynamic treatment of solid tumors with cascade activations. Upon light irradiation, our prodrug can effectively target the mitochondria of cancer cells, generate singlet oxygen to increase the level of reactive oxygen species (ROS) and trigger ROS-responsive release of CPT, which synergistically induce mitochondrial damage and cause the apoptosis of cancer cells, therefore achieving high therapeutic efficacy for solid tumors and minimized adverse effects to normal tissues. Our prodrug holds great promise as a potent and inspiring means for cancer treatment.